2019
DOI: 10.1587/transinf.2019mpp0005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Developer Commenting in Code Reviews

Abstract: Toshiki HIRAO †a) , Raula GAIKOVINA KULA †b) , Nonmembers, Akinori IHARA † †c) , Member, and Kenichi MATSUMOTO †d) , Nonmember SUMMARY Modern code review is a well-known practice to assess the quality of software where developers discuss the quality in a web-based review tool. However, this lightweight approach may risk an inefficient review participation, especially when comments becomes either excessive (i.e., too many) or underwhelming (i.e., too few). In this study, we investigate the phenomena of reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results indicate that useful comments share more vocabulary with the changed code, contain relevant code elements, and are written by more experienced reviewers. Similarly, another study found that experienced reviewers are capable of pointing out broader issues than inexperienced ones [131]. The study concluded that reviewer experience and patch characteristics such as commits with large and widespread modifications drive the number of comments and words in a comment [131].…”
Section: Support Systems For Codementioning
confidence: 92%
See 1 more Smart Citation
“…The results indicate that useful comments share more vocabulary with the changed code, contain relevant code elements, and are written by more experienced reviewers. Similarly, another study found that experienced reviewers are capable of pointing out broader issues than inexperienced ones [131]. The study concluded that reviewer experience and patch characteristics such as commits with large and widespread modifications drive the number of comments and words in a comment [131].…”
Section: Support Systems For Codementioning
confidence: 92%
“…Similarly, another study found that experienced reviewers are capable of pointing out broader issues than inexperienced ones [131]. The study concluded that reviewer experience and patch characteristics such as commits with large and widespread modifications drive the number of comments and words in a comment [131]. A study investigated the use of existing comments in code reviews [225].…”
Section: Support Systems For Codementioning
confidence: 99%